EFEKTIVITAS PENGELOLAAN SURAT MANUAL DAN DIGITAL DALAM MEWUJUDKAN TATA KELOLA ADMINISTRASI YANG AKUNTABEL DI DINAS PENDIDIKAN DIY - Shafa Cahyaningrum, Annisa; Hidayatullah, Hidayatullah; Saimin (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2025)
This study aims to analyze the effectiveness of manual and digital correspondence management in realizing accountable administrative governance at the Department of Education, Youth, and Sports of the Special Region of Yogyakarta (Disdikpora DIY). Using a qualitative descriptive approach, data were collected through direct observation, in-depth interviews, and documentation. The findings reveal that manual correspondence is still used, particularly for confidential letters or those requiring wet signatures, while the digital system via the SRIKANDI application enhances tracking capability, time efficiency, and archive security. The digital system supports administrative transparency and accountability by providing an auditable digital trail. However, the coexistence of manual and digital systems has led to work duplication and decreased efficiency. Other challenges include limited digital literacy, inadequate network infrastructure, and employee resistance to change. Therefore, sustainable human resource training, improved technological infrastructure, and strict internal policy are required to fully integrate the digital system. Such integration is essential to achieve modern, professional, and accountable public administration in alignment with good governance principles.